2019
DOI: 10.1029/2018ms001438
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Run‐Time Bias Correction for Antarctic Regional Climate Projections With a Stretched‐Grid AGCM

Abstract: This work presents snapshot simulations of the late 20th and late 21st century Antarctic climate under the RCP8.5 scenario carried out with an empirically bias-corrected global atmospheric general circulation model (AGCM), forced with bias-corrected sea-surface temperatures and sea ice and run with about 100-km resolution over Antarctica. The bias correction substantially improves the simulated mean late 20th century climate. The simulated atmospheric circulation of the bias-corrected model compares very favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 61 publications
5
26
0
Order By: Relevance
“…6) bear many similarities with the signature of a positive SAM pattern on Antarctic precipitation assessed in a RACMO2 ERA-Interim driven simulation in Marshall et al (2017). It is noteworthy that the link between circulation changes induced by the bias correction and ensuing precipitation changes seen in our simulations is very similar to the effect of bias corrections in the LMDZ model reported by Krinner et al (2019a).…”
Section: Surface Mass Balance and Precipitationsupporting
confidence: 80%
See 2 more Smart Citations
“…6) bear many similarities with the signature of a positive SAM pattern on Antarctic precipitation assessed in a RACMO2 ERA-Interim driven simulation in Marshall et al (2017). It is noteworthy that the link between circulation changes induced by the bias correction and ensuing precipitation changes seen in our simulations is very similar to the effect of bias corrections in the LMDZ model reported by Krinner et al (2019a).…”
Section: Surface Mass Balance and Precipitationsupporting
confidence: 80%
“…Larger differences in sea-level pressure projected changes found over the Pacific sector in our atmosphere corrected experiment are also consistent with this results from Bracegirdle et al (2013) who found that the historical state dependence was stronger in this area. In similar experiments conducted with LMDZ model (Krinner et al, 2019a) with different oceanic forcings, a smaller decrease (increase) of the high latitudes low (mid-latitudes highs) pressure is also found. The magnitude of these difference is however much more reduced when compared to the results with ARPEGE.…”
Section: Large-scale Atmospheric Circulationsupporting
confidence: 62%
See 1 more Smart Citation
“…All projections show a pressure increase at mid-latitudes (30-50 • S) and a decrease around Antarctica. This corresponds to a strengthening of the mid-to high-latitude pressure gradient (positive phase of the SAM) and a poleward shift of the circum-Antarctic low-pressure belt towards the continent, which are generally the expected consequences of 21st century radiative forcing (Kushner et al, 2001;Arblaster and Meehl, 2006). This pattern (increase at mid-latitude, decrease around Antarctica) is sharper in projections realised with MIROC-ESM SSCs.…”
Section: Atmospheric General Circulationmentioning
confidence: 91%
“…E is evaporation; P is precipitation; R is river runoff; B is Black Sea discharge into the Mediterranean Sea. OBS is a summary from Sanchez-Gomez et al (2011) for P , E and P -E, from Ludwig et al (2009) for R, from Lacombe and Tchernia (1972), Stanev et al (2000) and Kourafalou and Barbopoulos (2003) for B. River discharges in HIST are from the climatology of Ludwig et al, (2009). PICTRL uses the Nile of its preindustrial (pre-damming) value (2930 m 3 s −1 ) annually (Rivdis database; Vorosmarty et al, 1998).…”
Section: Mediterranean Thermohaline Circulationmentioning
confidence: 99%